Removal of heavy metals in textile wastewater by Ca-Alginate beads immobilized activated carbon - Abd Rahim, Muhammad Amirza; Abdullah, Shakila; Mohammad Razi, Mohd Adib (Penerbit UTHM, 2020)
Discharged of textile wastewater creates serious environmental problems. This paper investigates the ability of low-cost adsorbent to remove heavy metals present in the textile effluents. The Ca-alginate beads immobilized modified activated carbon (MACB) are considered as the potential adsorbent. Zinc (Zn) and Iron (Fe) present in the textile wastewater are considered as heavy metals pollutants. Batch adsorption studies are carried out to determine the heavy metals sorption capacity of MACB. The significant removal of Zn and Fe are 78% and 77%, respectively. Therefore, the low-cost adsorbent is determined to be cost-effective and efficient adsorbents in order to remove heavy metal pollutant from textile wastewater.